Popular History in the Classroom: Constructing a Narrative of National Identities in Britain - MULALIĆ, Lejla (Anafora, 2023)
This paper discusses the historical documentary as an increasingly popular and largely untheorised form of non-academic history. Placed between academic history and the popular medium of television and film, an authored historical documentary presented by a celebrity historian transcends various cultural binaries and demands to be considered on its own terms as a particular way of approaching history. Having in mind its subversive potential as well as its popular appeal, the paper is particularly concerned with the construction of national identities in the historical documentaries of Simon Schama (A History of Britain) and Michael Wood (The Great British Story), in order to elucidate the advantages of their use in the history classroom.Since every classroom exists within a particular socio-historical context, this discussion of British identities is positioned in the English Department’s history class in Sarajevo, within the context of post-war Bosnia and Herzegovina as a reminder that we never teach in a historical vacuum. While comparing Schama’s and Wood’s approaches to history, a number of questions emerge concerning the role of the historian in the construction of particular historical meanings; the use of narrative to present historical information; and the relevance of the documentary’s visual language in conveying specific interpretations of history. The paper attempts to answer these questions and explain how critical engagement with a historical documentary can help students learn not only about the content of history, but also about the processes behind the meanings we consume, which, ultimately, reveal a great deal about us as consumers.